SW1203-essays - Ingegerd Enström; Volodina Elena (University of Gothenburg, 2024)
For access please contact Ingegerd Enström.

För åtkomst kontakta Ingegerd Enström.
SW1203-uppsatser
Keywords: Language Technology (Computational Linguistics); L2; language learning; essays; corpus; Languages and Literature; Språk och litteratur; Natural Language Processing; Språkbehandling och datorlingvistik